Effect of a Bone Marrow-Derived Extracellular Matrix on Cell Adhesion and Neural Induction of Dental Pulp Stem Cells - Laudani, Samuele; La Cognata, Valentina; Iemmolo, Rosario; Bonaventura, Gabriele; Villaggio, Giusy; Saccone, Salvatore; Barcellona, Maria Luisa; Cavallaro, Sebastiano; Sinatra, Fulvia (Frontiers in Cell and Developmental Biology, 2020)
Extracellular matrix (ECM) represents an essential component of the cellular niche. In this conditioned microenvironment, proliferation rate and differentiation states of stem cells are regulated by several factors. On the contrary, in in vitro experimental models, cell growth or induction procedures towards specific cell lines usually occur in contact with plastic, glass or biogel supports. In this study, we evaluated the effect of a decellularized ECM, derived by bone marrow stem cells, on neuronal differentiation of mesenchymal stem cells extracted from dental pulp (Dental Pulp Stem Cells - DPSCs). Since DPSCs derive from neuroectodermal embryonic precursors, they are thought to have a major propensity towards the neuronal differentiation than mesenchymal stem cells isolated from other sources. We hypothesized that the presence of a decellularized ECM scaffold could act positively on neuronal-DPSCs differentiation through reproduction of an in vivo-like microenvironment. Results from scanning electron microscopy, immunofluorescence and gene expression assays showed that ECM is able to positively influence the morphology of cells, their distribution and the expression of specific neuronal markers (i.e. NF-L, NF-M, NF-H, PAX6, MAP2).